Enhancing government communication for climate change adaptation: a case study of agricultural policies and practices - Hasanah, Khuswatun; Brotodjojo, Rukmowati; Poerwanto, Mofit Eko; Lakatos, László (Interaksi: Jurnal Ilmu Komunikasi, 2025)
Climate change presents serious threats to highland agricultural areas such as Dieng (Central Java) and Karo (North Sumatra), where farmers increasingly experience irregular weather patterns, prolonged droughts, and frost events (bun upas). This study examines how the government communicates climate adaptation innovations—particularly through the Farmer Field School (Sekolah Lapang, SL) program and the work of agricultural extension officers (Penyuluh Pertanian Lapangan, PPL)—to support farmers in these vulnerable regions. Innovations such as the application of Lactic Acid Bacteria (LAB), Plant Growth-Promoting Rhizobacteria (PGPR), and basic frost prevention strategies have been introduced since 2022 through Farmer Field School (SL) initiatives led by local agricultural departments. Guided by Rogers’ Diffusion of Innovation Theory, this qualitative research involved semi-structured interviews with six farmers and two Agricultural Extension Officers. The analysis focuses on five diffusion stages: knowledge, persuasion, decision, implementation, and confirmation. The findings show that while farmers in both regions are increasingly aware of climate change (knowledge stage), many receive information from peers or media rather than official channels. In Dieng, adoption is constrained by resource competition with tourism and limited frost response strategies. In Karo, although media use is higher, government messaging still lacks practical, region-specific guidance. The study reveals key gaps in the persuasion and implementation phases, suggesting that existing communication efforts remain too generic and insufficiently persuasive. It recommends more localized, trust-based, and multi-channel communication strategies tailored to the unique environmental conditions of each region. The research contributes to the understanding of how institutional communication can better support innovation adoption in climate-vulnerable farming communities.